Integrating Coding and Artificial Intelligence in Indonesian Schools: A Systematic Literature Review of Needs and Curriculum Frameworks (2015–2024) - Syahril Chaniago; Heriyanto Heriyanto; Siti Alawiyah; Suci Khairunnisa (Universitas Lambung Mangkurat, 2025)
The integration of coding and Artificial Intelligence (AI) into primary and secondary education has transitioned from an option to an imperative in the digital era. This systematic literature review (SLR), guided by the PRISMA framework, synthesises global evidence to identify the core requirements for implementation and the characteristics of effective integrative curricula in the Indonesian context. Our analysis of 25 peer-reviewed studies revealed that successful integration is contingent upon four fundamental pillars: comprehensive teacher professional development, developmentally appropriate curriculum design, strategic technological infrastructure, and robust assessment frameworks. Furthermore, effective curricula are characterised by progressive and interdisciplinary integration, a strong emphasis on ethical considerations, and the use of engaging pedagogical approaches, such as project-based and game-based learning. Although international best practices provide valuable models, Indonesia still faces significant challenges related to resource equity and teacher readiness. This review concludes by proposing a phased implementation framework and outlining critical future research directions to bridge the gap between policy ambitions and classroom realities, thereby equipping Indonesian students with essential 21st-century competencies.